Effect of Transcriptional Regulator ID3 on Pulmonary Arterial Hypertension and Hereditary Hemorrhagic Telangiectasia - Vincent Avecilla (International Journal of Vascular Medicine)
Pulmonary arterial hypertension (PAH) can be discovered in patients who have a loss of function mutation of activin A receptor-like type 1 (ACVRL1) gene, a bone morphogenetic protein (BMP) type 1 receptor. Additionally, ACVRL1 mutations can lead to hereditary hemorrhagic telangiectasia (HHT), also known as Rendu-Osler-Weber disease, an autosomal dominant inherited disease that results in mucocutaneous telangiectasia and arteriovenous malformations (AVMs). Transcriptional regulator Inhibitor of DNA-Binding/Differentiation-3 (ID3) has been demonstrated to be involved in both PAH and HTT; however, the role of its overlapping molecular mechanistic effects has yet to be seen. This review will focus on the existing understanding of how ID3 may contribute to molecular involvement and perturbations thus altering both PAH and HHT outcomes. Improved understanding of how ID3 mediates these pathways will likely provide knowledge in the inhibition and regulation of these diseases through targeted therapies.